Final exit - Diaz, Lena (Diaz, Lena. EXIT Inc. series., 2017)
"After a tragic mistake nearly destroyed his life, Special Agent Kade Quinn will do whatever it takes to save his career. His latest mission? Track and capture the remaining EXIT operatives to determine if they're still a threat. But his next target--a stunning female assassin--is both elusive and dangerously appealing. Bailey Stark has outsmarted the FBI so far, but she's tired of running. Tired of watching her friends ambushed by government agents in tactical gear and never seen again. She suspects they aren't being evaluated--they're being exterminated--and she's determined to convince Agent Quinn his mission is a lie before it's too late. Bailey doesn't want to rely on him. She definitely shouldn't desire him. But she knows teaming up with the skilled, sexy agent may be her only hope. Kade doesn't want to believe Bailey's claims, but he promises to keep her safe. Trusting one another is difficult. Fighting their attraction is harder. And as they uncover the disturbing truth behind his mission . . . staying alive will be nearly impossible."--Back cover.